Malignant epithelial/exocrine tumors of the pancreas: Review - Luchini, Claudio; Grillo, Federica; Fassan, Matteo; Vanoli, Alessandro; Capelli, Paola; Paolino, Gaetano; Ingravallo, Giuseppe; Renzulli, Giuseppina; Doglioni, Claudio; D'Amuri, Alessandro; Mattiolo, Paola; Pecori, Sara; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Pancreatic malignant exocrine tumors represent the most important cause of neoplasm-related death for pancreatic neoplasms. The most common tumor type in this category is represented by pancreatic ductal adenocarcinoma (PDAC), an ill defined, stroma-rich, scirrhous neoplasm with glandular differentiation. Here we also present the relevant characteristics of the most important PDAC variants, namely adenosquamous carcinoma, colloid carcinoma, undifferentiated carcinoma, undifferentiated carcinoma with osteoclast-like giant cells, signet ring carcinoma, medullary carcinoma and hepatoid carcinoma. The other categories of malignant exocrine tumors, characterized by fleshy, stroma-poor, circumscribed neoplasms, include acinar cell carcinoma (pure and mixed), pancreatoblastoma, and solid pseudopapillary neoplasms. Here we present and discuss the most important macroscopic, histologic, immunohistochemical and molecular hallmarks of all these tumors, highlighting their key diagnostic / pathological features. At last, standardized indications regarding how to compile a formal pathology report for pancreatic malignant exocrine tumors will be provided.